The Association of Acquired Resistance EGFR Exon 20 T790M Mutation and Treatment Response in Lung Adenocarcinoma Patients Receiving EGFR-TKI: Relationship between Acquired Resistance T790M Mutation and RECIST 1.1 - Muhammad Harbi Praditya; Noni Novisari Soeroso; Setia Putra Tarigan; Taufik Ashar (Indonesian Society of Respirology (ISR), 2022)
Background: Lung adenocarcinoma patients receiving EGFR-TKI may develop acquired resistance within 7-16 months of treatment initiation, which is characterized by the presence of exon 20 T790M mutations in treatment response patients and can be assessed objectively by CECT and then evaluated by RECIST 1.1. The purpose of this study is to look into the association between acquired resistance EGFR Exon 20 T790M mutation and treatment response in lung adenocarcinoma patients receiving EGFR-TKI. Method: This research is an analytic study with a retrospective cohort design carried out at the Oncology Polyclinic at Haji Adam Malik Hospital from October 2020 to January 2021 in all patients with adenocarcinoma lung cancer who were treated with EGFR-TKI for more than 6 months. After that, an evaluation was carried out based on RECIST 1.1 and then examined for EGFR mutations from liquid biopsy specimens in the form of circulating tumor plasma DNA (ct-DNA) with the droplet digital Polymerase Chain Reaction (ddPCR) method to detect EGFR exon 20 T790M mutations as a marker of acquired resistance. Results: It was found that the majority of subjects were female (64.5%), aged 20-69 years (58%), and non-smokers (67.7%). The most common EGFR mutation was exon 19 deletion (58.1%). The incidence of acquired resistance was found in 10 subjects (32.3%). The distribution of RECIST 1.1 results on positive acquired resistance includes progressive diseases of 35.2%; stable disease of 11.1%; partial response of 33.4%; and 100% complete response. Negative acquired resistance includes 64.8% progressive disease, 88.9% stable disease, 66.6% partial response, and 0% complete response (P=0.93). Conclusion: There is no significant association between the incidence of acquired resistance mutations EGFR exon 20 T790M and treatment response in patients with lung adenocarcinoma who received EGFR-TKI therapy.